Comparison of biomechanical properties between post penetrating keratoplasty and deep anterior lamellar keratoplasty in keratoconus patients using ocular response analyser - Nawaz, Shah; Ahmad Sofi, Ishfaq; K. Maharana, Prafulla; Shaveta, Shaveta (International Journal of Medical Research and Review, 2015)
Introduction: Corneal biomechanics have been studied over recent years. The Ocular Response Analyser (ORA) is the first simple device able to measure the biomechanical properties of the cornea. Deep anterior lamellar keratoplasty (DALK) is considered an alternative procedure to penetrating keratoplasty (PK) in advanced keratoconus patients that leaves the host corneal endothelium and Descemet’s membrane intact. This provides thea dvantage of an absence of potential corneal endothelial rejection. The aim of the study was to compare the biomechanics between the two keratoplasty techniques. Method: This prospective comparative study included 150 eyes of150 patients. Patients were divided into 3 groups. 50 eyes with no previous surgery (Group1), 50 eyes of post PK (Group2) and 50 eyes of post DALK (Group 3) in advanced keratoconus patients were included in the study. Corneal Hysteresis (CH), corneal resistance factor (CRF), Goldmann- correlated intraocular pressure (IOPg) and corneal compensated intraocular pressure (IOPcc) was measured using Reichert ocular response analyser at 1 year follow up. Results: Mean age of the patients in PK group was 24.2±6.83 years and 20.95±6.49 yrs in DALK group ( p value < 0.126 , statistically insignificant). Mean CH in control group (10.9±1.42) and DALK group (10.5±3.79) was significantly higher than PK group(9.1±2.36)( p value < 0.01). Mean CRF in control group (10.6±2.56) and DALK group (10.1±3.2) was significantly higher than PK group (8.87±2.68) ( p value <0.01). However in these groups no statistically significant difference was seen in IOPcc and IOPg. Conclusions: Corneal biomechanical properties in post penetrating keratoplasty and lamellar procedures differ significantly.